Challenges and Advances in Medical Education Conference & Summer Institute - Violato, Claudio (Revue canadienne de l'éducation médicale, 2010)
CALL FOR PAPERS Deadline: May 15, 2010 3 3 rd International Congress in Medical Education Sponsored by Medical Education Research Centre, Università Ambrosiana International Graduate Medical Education Program Medical Education Research Unit, University of Calgary Followed by a Summer Institute in Medical Education, July 19-23